Influence of the Physical State of Spray-Dried Flavonoid-Inulin Microparticles on Oxidative Stability of Lipid Matrices - Gimenez-Castillo, B (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
The effect of the physical state of flavonoid-inulin microparticles (semi-crystalline/ amorphous) on the oxidative stability of lipid matrices was studied. Epicatechin (E) and quercetin (Q) microparticles with inulin were formulated at two infeed temperatures (15 ffC and 90 ffC) by spray drying. X-ray diffraction analyses showed that flavonoid-inulin microparticles obtained at feed temperature of 15 ffC were semi-crystalline (E-In-15, 61.2% and Q-In-15, 60%), whereas those at 90 ffC were amorphous (Q-In-90, 1.73 and Q-In-90 2.30%). Semi-crystalline state of flavonoid-inulin microparticles enhanced the EE (68.8 and 67.8% for E and Q, respectively) compared to amorphous state (41.6 and 51.1% for E and Q, respectively). However, amorphous Q-microparticles showed the highest antioxidant activity both in methyl linoleate and sunflower oil, increasing the induction period and decreasing the polar compounds and polymer triglyceride formation during long-term oxidation study. Therefore, the physical state of spray-dried flavonoid-inulin microparticles may determine their antioxidant activity in lipid matrices. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.